Visual outcomes with implantable Collamer lens versus small incision lenticule extraction in moderate-high myopia: A pilot study - Rajesh Sinha; Juhi Daga; Pranita Sahay; Vinay Gupta; Tushar Agarwal; Namrata Sharma; Prafulla K Maharana; Sudarshan K Khokhar; Jeewan S Titiyal (Indian Journal of Ophthalmology, 2025)
Purpose: To compare the visual outcomes of implantable Collamer lens (ICL) with small incision lenticule extraction (SMILE) in cases of moderate-high myopia. Methods: A prospective comparative study was conducted on 60 eyes of 30 patients with moderate-high myopia (−3D to −8D with astigmatism ≤1 D) at a tertiary eye care center. Patients underwent either SMILE or ICL in both eyes and had a postoperative follow-up of 1 year. Results: The manifest refractive spherical equivalent was −5.22 ± 1.05 D and −5.4 ± 1.17 D in the SMILE and ICL groups, respectively (P = 0.53). The mean sphere and cylinder were comparable between the groups. The mean uncorrected visual acuity improved from 1.18 ± 0.19 logMAR to 0.03 ± 0.07 logMAR in SMILE and 1.14 ± 0.25 logMAR to 0.011 ± 0.04 logMAR in the ICL group. The efficacy for SMILE was 83.3% and that for ICL was 93.3%. Safety and predictability (±0.5D) for both was 100%. A significant increase was observed in ocular aberration with a decrease in modular transfer function in the eyes that underwent SMILE, whereas no significant change in the eyes that underwent ICL. A significant difference was observed in all parameters of ocular aberration except corneal trefoil, corneal astigmatism, and PSF between the two groups at the final follow-up. The contrast sensitivity at final follow-up was higher in ICL cases when compared to SMILE. The quality of vision (QoV) score suggested a better QoV with ICL; however, the difference was not statistically significant. Conclusion: Both SMILE and ICL are safe in patients with moderate-high myopia. The efficacy, contrast sensitivity, and postoperative ocular aberration profile are better in cases undergoing ICL.